Karta wyników jako metoda wspomagająca efektywność realizacji strategii przedsiębiorstwa - Bernacka, Agnieszka (The Balance Scorecard as Method Helping Efficiency of Realization of Strategy Enterprise, 2005)
The paper presents the Balanced Score Card method, its meaning and structure. It shows its influence on creation and effective realization strategy of enterprise. The article is a kind of summary of already presented results of researches regarding the BSC method, its importance and effectiveness at the activity of the modern organization.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1061, s. 22-31